Environmental changes and human settlement in the central Marches (Italy) during the early-middle Holocene - Gilberto Calderoni; Giuseppe Cilla; Francesco Dramis; Cecilia Gobbi (Physio-Géo)
In the Early Holocene, the central Marches (Italy) underwent a widespread development of forest cover and soils which drastically reduced slope degradation and related aggradation processes in riverbeds. In such conditions, streams deeply incised the previous alluvial sediments. In the Apennine sectors, linear erosion was locally prevented by the growth of travertine dams in correspondence with river channel knickpoints and waterfalls. Fluvial deposition prevailed in the peri-Adriatic hilly belt, where river valleys still extended from the present coastline to the uprising Adriatic Sea, as testified by a 50-m-deep cored log, drilled near the Potenza River mouth. Several archaeological sites, ranging from the Mesolithic to the Aeneolithic, testify the recurrent presence of small-scale human groups on the alluvial plains of the lower valley sectors. Sandy-clayey sediments, emplaced by flooding episodes, repeatedly buried these settlements which were commonly located on the riversides. Small Aeneolithic communities were also present in the mountain sectors, around travertine-dammed swampy-lacustrine basins. On top of the sequences, Bronze Age sites were locally found. Widespread deforestation started in the early Iron Age (about 3000 yr BP), when alluvial plains and terraces were permanently occupied by large-scale human settlements. Geo-archaeological evidence of systematic deforestation at 2950 ± 50 14C yr BP, consisting of numerous round-shaped 1.5-3 m wide hollows, filled with soil sediments and upturned blocks of alluvial gravels, were found on top of a fluvial terrace in the Esino River basin. From the Iron Age to recent historical times, notwithstanding the progressive increase of debris supply to the drainage systems due to the spreading agricultural-pastoral activities, erosion dominated almost everywhere in the Marches rivers, likely induced by climatic factors.